Hormonal, Hematological, and Coagulation Dysregulation in Women with Toxoplasmosis with Associated Miscarriage (Journal of the College of Basic Education, 2026)
Toxoplasmosis is one of the most important health-threatening diseases with worldwide distribution and global impact, it is caused by Toxoplasma gondii (T. gondii). This study aimed to evaluate hormonal, hematological, and coagulation parameters in women with Toxoplasmosis associated miscarriage and to compare them with healthy controls. A case-control study was conducted on 100 aborted women attending Samarra General Hospital and private outpatient clinics in Samarra-Iraq between September 2025 and February 2026. The participants were divided into two main groups according to the results of serological examination for anti-Toxoplasma IgG and IgM antibodies: Patients group (n=50), and control group (n=50). Hormonal parameters, including prolactin and Growth Hormone, were measured. Hematological test indices such as Hemoglobin (Hb), Hematocrit (HCT), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) were assessed, along with White Blood Cell (WBC) and Platelet counts. Coagulation parameters, including prothrombin time (PT), partial Thromboplastin Time (PTT) and International Normalized Ratio (INR), were also evaluated using Enzyme-Linked Immunosorbent Assay (ELISA). Results show infected women showed higher prolactin level (45.73 ± 10.64 ng/mL) and lower growth hormone (1.325 ± 0.566 ng/mL) compared to control groups (38.38 ± 12.22 and 1.826 ± 0.827 ng/mL, respectively). Hematological parameters were reduced in patients, including hemoglobin (12.03 ± 1.67 g/dL), hematocrit (34.64 ± 2.82%), MCV (76.82 ± 9.18 fL), and MCH (26.80 ± 4.88 pg), compared to controls (14.50 ± 1.14 g/dL and 40.70 ± 2.62%). No significant differences were observed in WBC (6.79 ± 1.59 vs. 6.45 ± 1.65 ×10³/µL) and platelets (203.3 ± 41.7 vs. 216.6 ± 48.6 ×10³/µL). Coagulation parameters were elevated in patients, including PT (13.71 ± 0.44 sec), PTT (33.76 ± 2.53 sec), and INR (1.12 ± 0.10), compared to controls (12.52 ± 0.44 sec, 30.04 ± 3.00 sec, and 1.00 ± 0.04). The findings indicate that toxoplasmosis related with miscarriage and hormonal imbalances, haematological abnormalities, and coagulation disorders. These alterations may contribute to the pathophysiology of pregnancy loss and highlight the need for comprehensive evaluation in affected women